Functional Structure and Infrastructural Foundations of the Book Market in the Context of Transformation of the Cultural Space - I. V. BOHDAN (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article highlights approaches to interpreting the essence of the book market and the author proposes a generalized definition of the concept of the book market as a complex socio-economic system that encompasses a set of relations, institutions and mechanisms that ensure the creation, production, distribution and consumption of book products, as well as intellectual property rights.It is noted that an important aspect of the economic essence is the activity of market entities – publishing houses, printing companies, bookselling organizations, distributors and retail chains, where a system of interaction between market participants is formed in order to optimize their own costs, expand the range, improve the quality of products and take a stable position in a competitive environment.It is proven that the socio-cultural essence of the book market has a different nature, because a book is not only a product, but also a carrier of knowledge, culture, spiritual values and national identity.The economic functions of the book market are identified: a regulatory function, ensuring the establishment of a balance between demand and supply for book products; stimulating, aimed at the development of innovations in the field of book publishing; distributive - consists in regulating the movement of financial and material flows between the main market participants – publishing houses, printing enterprises, bookselling chains, libraries and end consumers. Along with this, the socio-cultural functions of the book market are considered: information function, which involves the dissemination of knowledge, ideas, cultural and scientific achievements; ideological or educational function, which consists in the formation of value orientations, worldview positions and national identity; socio-cultural function – socializing, which helps the individual to merge into the cultural space.The infrastructure of providing this market is outlined: the production infrastructure includes publishing houses, printing enterprises, design studios, as well as recording studios that create audiobooks; distribution infrastructure includes wholesale and retail distributors, warehouses, transport and logistics companies, bookstores, kiosks, chain supermarkets, as well as online sales platforms; information infrastructure is represented by bibliographic centers (in particular, the Book Chamber of Ukraine), electronic catalogs, databases, professional media; financial infrastructure, which includes banks, investment funds, state support programs (for example, the Ukrainian Book Institute), as well as charitable foundations and patronage initiatives.It is motivated that the effective implementation of these functions is possible only with a developed book market infrastructure: a set of institutions, systems and mechanisms that ensure the interaction of market entities.